Flow cytometric analysis of immune cell populations in the bronchial and mesenteric lymph nodes of the dromedary camel - Hussen, Jamal; Althagafi, Hind; Al-Sukruwah, Mohammed Ali; Falemban, Baraa; Abdul Manap, Aimi Syamima (Frontiers in Veterinary Science, 2024)
Dromedary camel is an important livestock species with special economic value in arid and semi-arid regions of the world. In this study, we applied flow cytometry and multicolor immuno-fluorescence to phenotype the main populations of immune cells in the bronchial and mesenteric camel lymph nodes and compared them with separated peripheral blood mononuclear cells and granulocytes. We used antibodies to detect several cell surface molecules associated with camel T cells (CD4, WC1), B cells (MHCII, BAQ44A), monocytes/macrophages (CD172a, CD14, CD163), in addition to the panleukocyte marker CD45 and the cell adhesion molecules CD44 and CD18. Compared to blood mononuclear cells, camel lymph node cells contained a higher percentage of lymphoid cells with only a minor fraction of myeloid cells. In addition, the lower expression of CD44 and CD18 on lymph node lymphocytes compared to lymphocytes from peripheral blood indicates higher frequency of naïve lymphocytes in the lymph nodes. The frequency of CD4 + T cells, B cells and γδ T cells within camel lymph node lymphocytes compared to blood indicates a similar tissue distribution pattern of lymphocyte subsets in camel and bovine and supports previous reports on the similarity between the camel immune system and the immune system of other ruminants Lymph node neutrophils were identified as CD45 ++ CD172a ++ , CD14 + , MHCII low , BAQ44A + , CD44 ++ , CD18 ++ cells. In conclusion, the present study is describing the employment of flow cytometric single-cell analysis and immunostaining for the analysis of the immune cell composition in the camel lymph node.